Single incision simultaneous liver kidney transplantation: Feasibility and outcomes. Issue 1 (25th November 2022) - Imai, Daisuke; Sambommatsu, Yuzuru; Sharma, Amit; Kumaran, Vinay; Cotterell, Adrian H.; Khan, Aamir A.; Lee, Seung Duk; Gupta, Gaurav; Levy, Marlon F.; Bruno, David A.
Abstract: Background: Traditionally, simultaneous liver kidney transplantation (SLK) has been performed using a subcostal incision for the liver allograft and a lower abdominal incision for kidney transplantation (dual incision, DI). At our institution, we performed SLK using a single subcostal incision (SI). The aim of this study was to report the outcomes of single versus dual incisions for SLK. Methods: A retrospective cohort study of consecutive SLK procedures performed at our center from January 2015 to April 2021 was performed. The demographic characteristics, complications, intraoperative findings, and complications after SI and DI were statistically compared. Results: A total 37 SLK were performed (19 DI and 18 SI). The age and indications for transplantation were comparable between the two groups. Patient in SI group had significantly higher MELD score (27.0 ± 1.5 vs. 31.7 ± 1.5, p = .038). The cold ischemic time of kidney transplantation (599 ± 26 min vs. 447 ± 27 min, p < .001) and the total surgical time (508 ± 21 min vs. 423 ± 22 min, p = .008) were significantly shorter in the SI group. The incidence of complications and post‐transplant kidney function was comparable between the groups. A slightly higher incidence of surgical site complications was noted in the DI group without any statistically significance ( p = .178). Conclusions: Single‐subcostal incision SLK is technically feasible and has comparable outcomes to dual‐incision SLK. SI was associated with shorter cold ischemic time for kidney transplant, as well as shorter overall operative time.